2019
DOI: 10.1021/acs.jpcc.9b00506
|View full text |Cite
|
Sign up to set email alerts
|

Titanylphthalocyanine Films on Ag(111): An Epitaxial Metal/Organic Heterosystem with an Exceptional Smooth Surface

Abstract: The fabrication of smooth organic semiconductor films with homogeneous thickness is of key importance for the improvement of organic electronic devices and realization of well-defined molecular heterostructures. Although many π-conjugated molecular materials form highly ordered monolayers on (single) crystalline metal substrates, further deposition typically obeys a Stranski–Krastanov growth and results in considerable layer roughness. Here, we examine the evolution of titanylphthalocyanine (TiOPc) films on Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Thus, despite the excellent longrange order of the Ag(111) surface, this superior ordering seems not to be continued in thicker films as it has been found for other molecular adlayers. 44,45 A possible reason for a broad distribution of fibre orientations could be the influence of surface defects such as step edges or kinks, which can cause parasitic nucleation and lead to deviant fibre growth, as shown before for the case of DNTT-fibres on Ag(111). 21 In that case, it was found that a step edge mediated growth could be efficiently suppressed by first exposing the sample to oxygen, which adsorbs preferentially at step edges 46,47 and thereby suppresses this specific nucleation.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, despite the excellent longrange order of the Ag(111) surface, this superior ordering seems not to be continued in thicker films as it has been found for other molecular adlayers. 44,45 A possible reason for a broad distribution of fibre orientations could be the influence of surface defects such as step edges or kinks, which can cause parasitic nucleation and lead to deviant fibre growth, as shown before for the case of DNTT-fibres on Ag(111). 21 In that case, it was found that a step edge mediated growth could be efficiently suppressed by first exposing the sample to oxygen, which adsorbs preferentially at step edges 46,47 and thereby suppresses this specific nucleation.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies revealed only short-range crystalline order for phthalocyanine films grown at room temperature without any subsequent annealing step, 38−40 which can be rationalized by the small diffusivity of these (heavy) molecules. For TiOPc films on Ag(111), this effect was examined in detail and distinct increases of the domain size and crystalline order were found when the substrate temperature was raised from 300 to 450 K. 41 Since defects such as grain boundaries in OSC films greatly reduce the charge carrier mobility, one of the challenges in organic electronics is the production of long-range ordered films with the lowest possible defect density. In order to identify the thermodynamically most stable seed layer structures that enable subsequent growth of extended crystalline domains, we first examined the TiOPc film growth at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have limited ourselves to substrate temperatures between 250 and 450 K to safely exclude a transition to the β-phase and still obtain crystalline films since growth at cryogenic temperatures yields very smooth but amorphous films as demonstrated before in the case of titanylphthalocyanine …”
Section: Resultsmentioning
confidence: 99%
“…Here, we have limited ourselves to substrate temperatures between 250 and 450 K to safely exclude a transition to the βphase and still obtain crystalline films since growth at cryogenic temperatures yields very smooth but amorphous films as demonstrated before in the case of titanylphthalocyanine. 49 For all investigated substrate temperatures, only one filmrelated diffraction peak was observed in the out-of-plane X-ray diffractograms (cf. Figure 1a), which was identified as the (112̅ ) CuPc reflection of the α-phase.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%